Monitoring and analysis of anomalous refraction using a digital zenith camera system - Hirt, Christian (EDP Sciences, 2006)
Context. Anomalous refraction is considered to be a limiting factor for ground-based astrometry in general and astrogeodetic observations in particular. Typical characteristics of anomalous refraction are basically known by means of spot-check-data, however the fluctuation is rather little studied. Aims. The goal of this study is to derive empirical knowledge on the fluctuation of anomalous refraction in the optical domain. Methods. A Digital Zenith Camera System usually applied for the astrogeodetic determination of the Earth's gravity field has been used for continuously monitoring anomalous refraction. With a sample frequency of about 2 observations per minute, about 7300 single observation epochs were collected during 6 nights. Residuals of the observations with respect to reference data show how anomalous refraction behaves. Results. The analysis of approximately 70 h of observational data reveals heterogeneous fluctuation patterns of anomalous refraction at the zenith. Wave-like and bump-like variations appear as well as slowly-changing, drift-like structures. With respect to its magnitude, the effect reaches from 0."05 up to about 0."2 at frequencies of some hours. Even much lower frequencies of anomalous refraction are indicated in the data sets causing an offset of about 0."04. The accuracy of the filtered data has been found to be about 0."05- 0."08. Conclusions. The study indicates how anomalous refraction may fluctuate. The results are considered to give an estimate of the accuracy limit for astrogeodetic and other absolute ground-based astrometric observations.